Heterozygous β-globin gene mutations as a risk factor for iron accumulation and liver fibrosis in chronic hepatitis C. Issue 5 (29th November 2006) - Sartori, Massimo; Andorno, Silvano; Pagliarulo, Michela; Rigamonti, Cristina; Bozzola, Cristina; Pergolini, Patrizia; Rolla, Roberta; Suno, Anna; Boldorini, Renzo; Bellomo, Giorgio; Albano, Emanuele
Abstract : Background: Iron accumulation is a well-known risk factor for the progression of chronic hepatitis C (CHC) to fibrosis. However, the profibrogenic role of the genes controlling iron homeostasis is still controversial. Aim: To evaluate the relative role of haemachromatosis (HFE), ferroportin and β-globin gene mutations in promoting iron accumulation and fibrosis in patients with CHC. Methods: Genetic analysis was performed together with the assessment of hepatic iron content and histology in 100 consecutive HIV-antibody and hepatitis B surface antigen-negative patients with biopsy-proven CHC. Results: Among the patients investigated, 12 were heterozygous for various β-globin gene mutations (39[C→T], IVS1.1[G→A], 22 7 bp deletion and IVS1.6[T→C]) and 29 carried HFE (C282Y, H63D and S65C) gene mutations. One further patient was heterozygous for both HFE (H63D) and β-globin (39[C→T]) variants, whereas 58 had the wild-type alleles of both the genes. Hepatic iron concentration (HIC) and hepatic stainable iron were significantly higher (p<0.05) in patients with CHC carrying β-globin mutations than in those with HFE mutations or the wild-type alleles. Multivariate analysis confirmed that the presence of β-globin mutations was independently associated with both HIC (p = 0.008) and hepatic-stainable iron (odds ratio (OR) 6.11; 95% CI 1.56 to 23.92; p = 0.009). Moderate/severe fibrosis or cirrhosis (Ishak's score >2) was observed in 48 of 100 patients. Logistic regression demonstrated that age (OR 1.05; 95% CI 1.02 to 1.09; p<0.005) and β-globin mutations (OR 4.99; 95% CI 1.22 to 20.3; p = 0.025) were independent predictors of the severity of fibrosis. Conclusions: Heterozygosis for β-globin mutations is a novel risk factor for both hepatic iron accumulation and the progression to fibrosis in patients with CHC.